Copper-exchanged large-port and small-port mordenite (MOR) for methane-to-methanol conversion. Issue 49 (20th September 2021) - Knorpp, Amy J.; Pinar, Ana B.; Newton, Mark A.; Li, Teng; Calbry-Muzyka, Adelaide; van Bokhoven, Jeroen A.
Abstract : The synthesis and selection of large-port mordenite is critical for optimizing productivity for the direct conversion of methane to methanol. Abstract : Zeolite mordenite (MOR) is one of the most studied zeolites for the stepwise direct conversion of methane to methanol, but it also can exist in two forms: large port and small port. Here we report that the synthesis and selection of the parent mordenite is critical for optimizing productivity, and that large-port mordenite outperforms small-port mordenite for the stepwise conversion of methane to methanol.